Iatrogenic premature ovarian failure prevention and fertility preservation methods for women who have been diagnosed with colorectal cancer - Žilinskas, Kastytis; Kairys, Ignas; Gudlevičienė, Živilė; Samalavičius, Narimantas Evaldas (Lietuvos chirurgija, 2016)
Introduction In the last 30 years it was identified an increased incidence of colorectal cancer in young woman. Those women who develop rectal cancer may necessitate use of chemotherapy and radiation therapy in combination. For this reason many young women face infertility and iatrogenic premature ovarian failure problems. They are not regularly informed about the risks of chemoradiotherapy on their reproductive system and the possibilities of fertility preservation and restoring ovarian function. So our aim is to introduce the Lithuanian society and our patients with fertility preservation possibility while treating rectal cancer, using ovarian transposition and ovarian tissue cryopreservation. Case report 27-year-old woman was diagnosed with rectal cancer in 2015.10.12. III clinical stage of rectal cancer was found using endoscopic and radiological tests. Multidisciplinary team discussed this case and decided to begin the treatment with neoadjuvant chemotherapy and radiotherapy after laparoscopic ovarian transposition and ovarian tissue cryopreservation, which was done in 2015.11.25. After that patient was treated with pre-operative chemoradiotherapy. On 2016.02.25 total mesorectal excision was removed and patient was set for adjuvant chemotherapy treatment. At the moment, patient‘s treatment is in motion. Conclusions By using combined fertility preservation techniques – ovarian transposition and ovarian tissue cryopreservation – we were able to offer the patient a possibility to avoid iatrogenic premature ovarian failure problems and preservation of ovarian function.
Keywords: ovarian tissue cryopreservation; ovarian transposition; colorectal cancer